Using the Sand Tray in the Context of the Latest Research in Neuroscience to Transform Clients’ Defences - De Little, Madeleine M. (Canadian Journal of Counselling and Psychotherapy, 2020)
Current research and theories of neuroscience are woven together with Satir psychotherapy and sand tray therapy in this author-developed therapeutic approach called “Neuroscience and Satir in the Sand Tray” (NSST). The theory and the practice of all three parts of NSST are explained and elucidated. This therapeutic approach achieves the transformation of the defences by eliciting the projective identification into figurines and the subsequent enactments(s) that bring about profound “aha” moments of transformation. An example of transformation in the sand tray is presented with photographs. It recounts an NSST training session with a young adult counsellor who created a scene in the sand tray of a highly defended little boy (figurine) and announced that this defensive protection would “never come off.” This article illustrates how such strong, familiar patterns of protection can be transformed within the sand tray before occurring in the body so that the client can experience themselves as being different at a cellular level through epigenetics.